Initial Characterization of Stressed Transgenic Mice With Cardiomyocyte-Specific Overexpression of Protein Phosphatase 2C - Bollmann, Paula; Werner, Franziska; Jaron, Marko; Bruns, Tom A.; Wache, Hartmut; Runte, Jochen; Boknik, Peter; Kirchhefer, Uwe; Müller, Frank U.; Buchwalow, Igor B.; Rothemund, Sven; Neumann, Joachim; et al. (Frontiers in Pharmacology, 2021)
As part of our ongoing studies on the potential pathophysiological role of serine/threonine phosphatases (PP) in the mammalian heart, we have generated mice with cardiac-specific overexpression of PP2Cβ (PP2C-TG) and compared them with littermate wild type mice (WT) serving as a control. Cardiac fibrosis was noted histologically in PP2C-TG. Collagen 1a, interleukin-6 and the natriuretic peptides ANP and BNP were augmented in PP2C-TG versus WT (p<0.05). Left atrial preparations from PP2C-TG were less resistant to hypoxia than atria from WT. PP2C-TG maintained cardiac function after the injection of lipopolysaccharide (LPS, a model of sepsis) and chronic isoproterenol treatment (a model of heart failure) better than WT. Crossbreeding of PP2C-TG mice with PP2A-TG mice (a genetic model of heart failure) resulted in double transgenic (DT) mice that exhibited a pronounced increase of heart weight in contrast to the mild hypertrophy noted in the mono-transgenic mice. The ejection fraction was reduced in PP2C-TG and in PP2A-TG mice compared with WT, but the reduction was the highest in DT compared with WT. PP2A enzyme activity was enhanced in PP2A-TG and DT mice compared with WT and PP2C-TG mice. In summary, cardiac overexpression of PP2Cβ and co-overexpression of both the catalytic subunit of PP2A and PP2Cβ were detrimental to cardiac function. PP2Cβ overexpression made cardiac preparations less resistant to hypoxia than WT, leading to fibrosis, but PP2Cβ overexpression led to better adaptation to some stressors, such as LPS or chronic β-adrenergic stimulation. Hence, the effect of PP2Cβ is context sensitive.